Use of epidermal characters as bioindicators of environmental pollution - Arriaga, Mirta Olga (2014)
The present study explores the use of micromorphological leaf epidermal characters of Ficus benjamina (evergreen) and Fraxinus pennsylvanica (deciduous) as indicators of pollution in the Metropolitan Area of Buenos Aires. Mature leaves of both species were sampled along an urbanperiurban gradient, with a rural area as control for epidermal characters. Parameters examined from abaxial and upper epidermis were: (1) length and width of stomata, (2) number of stomata per area unit, (3) length and width of epidermal cells, (4) number of epidermal cells per area unit. Data were analysed with basic statistical and multivariate techniques. Principal Component Analysis (PCA) clearly grouped foliar samples according to three zones: urban, periurban and rural areas with different pollution values. No correlations were observed between epidermal character variations and climate variables, air pollutants or C, N, P and metals concentration in soil. Only one positive correlation (p=0.006) was found between stomata length in leaves from Ficus and iron concentration in soil.